1991
DOI: 10.1007/bf00185837
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the tracheal muscle in developing, adult and ageing guinea-pigs

Abstract: The musculature of the trachea of adult guinea-pigs is ultrastructurally similar to other visceral muscles. However, tracheal muscle cells have irregular outlines, large accumulations of glycogen, a small number of gap junctions, and many small elastic fibres and collagen fibrils (50 nm in diameter). Fibroblasts, mast cells, Schwann cells and axons are found within the muscle, but no interstitial cells. Capillaries run in the connective tissue septa. The tracheal muscle is well differentiated at the end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In rat aortas, the basal lamina is relatively scant at birth (4,17). Basal lamina thickening has also been noted in developing guinea pig tracheal muscle (5,9). In the present study, SMC basal lamina thickness increased 114% from 140 GD to the adult ( Table 2).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In rat aortas, the basal lamina is relatively scant at birth (4,17). Basal lamina thickening has also been noted in developing guinea pig tracheal muscle (5,9). In the present study, SMC basal lamina thickness increased 114% from 140 GD to the adult ( Table 2).…”
Section: Discussionsupporting
confidence: 65%
“…Several workers have described the architecture of the arterial wall (3), as well as the ultrastructure of SMCs per se (9). Nonetheless, surprisingly few reports have described the ontogeny of SMC development in a particular vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, it has been reported that elastin content and hydroxyproline content per dry tissue weight did not change in BALB/c mice and SAMR1 rats during aging (Takubo et al, 1999). Furthermore, morphological alteration of smooth muscle cells (SMCs) in the aging airway was also reported in guinea pig trachea (Gabella, 1991). In 30-to 36-month-old guinea pigs, deep invagination and irregular profiles of the cellular membrane were demonstrated in SMCs.…”
mentioning
confidence: 99%
“…They suggested a correlation between the distribution of the fibrils, biochemical conditions and the functional loading of the tissue. Different diameters of collagen fibrils have been reported in various tissues including cartilage [19][20][21], subepithelial connective tissue of oral mucosa [22,23], eye [24,25], peripheral nerve [26,27], skeletal muscle [28,29] and tendon [30][31][32]. From studying these works, it seems that collagen fibers generally have a large diameter in tendons and sclera, where they are exposed to substantial mechanical stress.…”
Section: Discussionmentioning
confidence: 99%